Impact of oil prices on the Islamic and conventional stock indexes’ performance in Malaysia during the COVID-19 pandemic: Fresh evidence from the wavelet-based approach - Khan, Ali Burhan; Sharif, Arshian; Islam, Muhammad Saif Ul; Ali, Anis; Fareed, Muhammad; Zulfaqar, Maria (Frontiers in Energy Research, 2022)
The motivation behind conducting this research is to study the association between oil prices and Islamic and conventional stock indexes’ performance in the Malaysian market during COVID-19 using the wavelet analysis technique. The daily data on selected variables were collected from 1 January 2020, to 10 June 2021. Empirical investigation was made with wavelet analysis along with the Toda-Yamamoto test. The results revealed the significant response of both indexes to the oil price. Such response was negative for the short- and medium terms; however, it became positive in the long run. Our research has several important implications and recommendations for asset managers and policymakers. Policymakers and regulators should promote awareness and adopt effective action plans to minimize the risk of change in oil prices during the COVID-19 period. This research will enable investors, scholars, and policymakers to improve their current structure and prepare them for any potential future crisis.